1999
DOI: 10.1021/om980863p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Reactivity of [LiC(SiMe2H)3]·2THF:  Formation of 1,1,3,3-Tetramethyl-2,2,4,4-tetrakis(dimethylsilyl)- 1,3-disilacyclobutane, [Me2SiC(SiMe2H)2]2

Abstract: Reaction of [HC(SiMe2H)3] with [(CH3)2CH]2NLi in tetrahydrofuran afforded [LiC(SiMe2H)3]·2THF (1) in excellent yield. Reactions of 1 with Me3SiCl, MeSiHCl2, HSiCl3 and MeSiCl3 at −78 °C gave [Me3SiC(SiMe2H)3] (2), [(HMeClSi)C(SiMe2H)3] (3), [(HCl2Si)C(SiMe2H)3] (4), and [(MeCl2Si)C(SiMe2H)3] (5), respectively. At room temperature, reaction between 1 and SiCl4 in toluene resulted in multiple products, including a new highly substituted 1,3-disilacyclobutane [Me2SiC(SiMe2H)2]2 (6). 6 was isolated in moderate yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…In our hands, however, 1 did not react with LiNPr i 2 in heptane/THF, either under the conditions employed previously in the metallation of (HMe 2 Si) 3 CH [24], or under reflux. It did however react with methyllithium in THF to give a good yield of the THF adduct 2a.…”
Section: The Lithium Derivatives 2a Andmentioning
confidence: 45%
See 2 more Smart Citations
“…In our hands, however, 1 did not react with LiNPr i 2 in heptane/THF, either under the conditions employed previously in the metallation of (HMe 2 Si) 3 CH [24], or under reflux. It did however react with methyllithium in THF to give a good yield of the THF adduct 2a.…”
Section: The Lithium Derivatives 2a Andmentioning
confidence: 45%
“…It was not isolated but treated at once with zinc or cadmium halides to give the dialkyl compounds M{C(SiMe 3 ) 2 (SiMe 2 H)} 2 (M ¼ Zn or Cd) [23]. We considered that a more convenient synthesis would be from 1 and lithium diisopropylamide, since the compound Li(THF) 2 {C(SiMe 2 H) 3 } (10a) can be readily obtained in this way [24].…”
Section: The Lithium Derivatives 2a Andmentioning
confidence: 99%
See 1 more Smart Citation
“…While HC(SiHMe 2 ) 3 18 reacts readily with lithium diisopropylamide, 19 A single-crystal X-ray diffraction study revealed a polymeric structure for 2ÁTMEDA, ‡ with each K cation interacting with two C(SiHMe 2 ) 2 Ph groups ( Fig. 1) through the H1s (2.82(4) Å), the C6 and C11 (from a phenyl group) of one ligand, and the C9 and C10 from a phenyl of the second.…”
Section: (1)mentioning
confidence: 99%
“…It is also known that [(HSiMe 2 ) 3 CLi].2THF is formed in excellent yield from the reaction of (HSiMe 2 ) 3 CH with (Me 2 CH) 2 NLi in THF [4]. Attachment of tris(trimethylsilyl)methyl groups to macromolecular chains leads to important modifications of polymer properties such as potential membrane materials in separation processes and an increase in glass transition temperature [5][6].…”
Section: Introductionmentioning
confidence: 99%